2017
DOI: 10.18502/kls.v2i6.1088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Food Security Determinants Among Rice Farming Households in Bali Province

Abstract: This study aimed to investigate food security at household level and to identify the socio-economic factors that affect the levels of food security among households of lowland rice farmers. Research was conducted in three district centers of rice production in the province of Bali, i.e. Buleleng, Gianyar and Tabanan. Samples were taken by multistage sampling of 216 respondents consisting of 122 farmers ICM program and 94 farmers non-ICM program. The data for the study were obtained with the aid of a structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…However, compared to findings reported in various studies, the number of households with food secure status in the present study was much higher. For example, the reported proportion of food-secure households in Nigeria varied from 12.44% (Ibok et al, 2014) Indrasti, 2017). The methodologies applied for measuring food security in some of those studies were different from that used in the present study, but still the percentage of food secure households in the study area was very high particularly in the context of poor cassava-growing households in rural areas.…”
Section: Household Food Security Statusmentioning
confidence: 59%
“…However, compared to findings reported in various studies, the number of households with food secure status in the present study was much higher. For example, the reported proportion of food-secure households in Nigeria varied from 12.44% (Ibok et al, 2014) Indrasti, 2017). The methodologies applied for measuring food security in some of those studies were different from that used in the present study, but still the percentage of food secure households in the study area was very high particularly in the context of poor cassava-growing households in rural areas.…”
Section: Household Food Security Statusmentioning
confidence: 59%
“…Using Tobit regression model, the study found evidence that gender, family size, level of enlightenment, nuptial position, family income capacity, agricultural experience and livestock ownership had weighty influences on food security of a family. Suharyanto and Indrasti (2017) carried out a research to determine factors that influenced food security in the Province of Bali by using Buleleng, Gianyar and Tabanan districts. The study found that about 49.07% of the households were food secure, 37.9% were at risk of food insecurity, 8.79% were already food deficient while 4.17% were adjudged food insecure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the study, the model in question was used to analyze the effects of agricultural businesses and demographic features on the tendency of growers to choose direct marketing channels in cherry selling. Suharyanto and Indrasti (2017) also applied the ordered logistic regression model in a study entitled "Assessment of food security determinants among rice farming households in Bali province." In the study, socioeconomic factors that affected household food security levels were estimated using ordered logistic regression.…”
Section: Ordered Logistic Regression (Olr)mentioning
confidence: 99%